Skills to Enhance Positivity in Suicidal Adolescents: Results From an Open Development Trial. Issue 2 (March 2019) - Yen, Shirley; Ranney, Megan L.; Tezanos, Katherine M.; Chuong, Adam; Kahler, Christopher W.; Solomon, Joel B.; Spirito, Anthony
"Skills to Enhance Positivity" (STEP) is a two-part positive affect program designed to decrease recurrent suicidal behavior in adolescents hospitalized due to suicide risk. Here, we describe the initial pilot phase in which the intervention was developed and modified based on a sample of 20 adolescent participants, aged 12 to 18 years old ( M age = 15.9, SD = 1.5). STEP consisted of an in-person phase (four sessions) and a remote delivery phase (text messaging and phone calls). The inpatient sessions focused on psychoeducation of positive affect, mindfulness meditation, gratitude, and savoring. The remote delivery phase comprised of weekly phone calls and daily text messages to enhance mood monitoring and skills practice reminders. Average session attendance was 81%, and mean daily response rate to text messages was 73.6%, demonstrating high engagement. STEP was described as good or excellent by over 90% of parents and 100% of adolescents. Only one participant had a suicide attempt, and five were readmitted for suicidality in the following 6 months, fewer than comparable naturalistic studies. Although preliminary results are promising, larger randomized trials are needed to determine the efficacy of STEP in reducing suicidal behaviors.